STRATEGIES FOR DEVELOPING RELIGIOUS CULTURE TO SHAPE, THE CHARACTER OF STUDENTS - Wening, Muslimah Hikmah; Hasanah, Enung (Universitas Ahmad Dahlan, 2020)
Religious culture is applied in schools so that the good habits of students, so that the strategy of developing religious culture is essential to be applied to schools so that students have a noble character in Islamic education. The purpose of this study is to describe the strategy of developing a religious culture to shape students' character. This research is qualitative. Data collection obtained through in-depth interviews, observation, and documentation studies. This study's subject was determined based on a purposive sampling technique with information from the homeroom teacher. Checking the validity of the data starts with using a check and continues with the triangulation technique. The results showed that the strategy of developing a culture of religious and improving the character of students at SD Muhammadiyah Tonggalan, 1) creating a religious atmosphere in schools including allocating half an hour to learn to read the Qur'an before the lesson begins, do the Dhuha, Dhuhr, Asr prayer,Â Ramadan fasting, qurban worship, hajj rituals, social services, Sunday morning teachings,Â also (2) habituation of Islamic values. The research findings expected to illustrate that the strategy of developing religious culture can shape students' character.